Role of Organizations in skill Development Program in India - Pandey, Dr Tarkeshwar (IJRDO - Journal of Applied Management Science, 2016)
Skill development and entrepreneurship efforts across the country have beenhighly fragmented so far. As opposed to developed countries, where the percentage of skilledworkforce is between 60% and 90% of the total workforce, India records a low 5% of workforce(20-24 years) with formal vocational skills. There is a need for speedy reorganization of theecosystem of skill development and entrepreneurship promotion in the country to suit the needsof the industry and enable decent quality of life to its population.Today, more than 20 Ministries/Departments run 70 plus schemes for skill development in thecountry. However, there are gaps in the capacity and quality of training infrastructure as well asoutputs, insufficient focus on workforce aspirations, lack of certification and common standardsand a pointed lack of focus on the unorganized sector.Recognizing the need and urgency of quickly coordinating the efforts of all concernedstakeholders in the field of Skill Development and Entrepreneurship, Government of Indianotified the formation of the Department of Skill Development and Entrepreneurship on 31stJuly, 2014 which subsequently led to the creation of the Ministry of Skill Development andEntrepreneurship on 10th Nov, 2014